Implementation, implementation, implementation: Old and new options for putting surveys and experiments online - George MacKerron (Journal of Choice Modelling, 2011)
The Internet offers enormous possibilities for surveys and experimental data collection, including randomised treatments, customisation, and interactivity. These capabilities are well suited to the implementation of choice modelling experiments. However, the implementation of web surveys is not a simple task, and the existing options open to researchers are commonly unsatisfactory in a number of ways. The result is that few Internet surveys and experiments are able to exploit the unique capabilities of the web. This paper suggests a new approach, illustrated with a working prototype: an open-source, domain-specific language (DSL) designed for specifying web surveys and experiments, which is called websperiment. The paper rst looks at the existing approaches, highlighting their strengths and weaknesses. It then outlines the concepts underlying websperiment, and this DSL's nature and scope, with simple code examples. Finally, it shows how the DSL can be used to concisely specify a highly dynamic choice modelling survey.
Keywords: 330; survey; questionnaire; choice experiment; internet; implementation; DSL; Ruby